Enhancement of crystallization kinetics of poly(l-lactic acid) by grafting with optically pure branches. (16th June 2021) - Longo, Alessandra; Dal Poggetto, Giovanni; Malinconico, Mario; Laurienzo, Paola; Di Maio, Ernesto; Di Lorenzo, Maria Laura
Abstract: This work details the first example of enhancement of crystallization rate of poly (l -lactic acid) (PLLA) by introducing optically pure short chain branches. A biobased PLLA copolymer was prepared by initial radical functionalization of commercial PLLA with itaconic anhydride (IAH) in a Brabender mixer, then by reaction with a tailor-made hydroxyl-terminated, optically pure PLLA with molar mass M n  = 4 kDa, the latter prepared via ring opening polymerization. Gel permeation chromatography and infrared spectroscopy proved the efficiency of grafting reaction, with the amount of grafted IAH quantified via UV–Vis. The synthesized graft copolymer displays faster crystallization rate with respect not only to the commercial grade, but also to a binary blend with the same nominal composition. The role played by the short branches in favoring both crystal nucleation and growth was discussed in terms of molecular nucleation. The results detailed in this manuscript demonstrate that synthesis of a graft copolymer with optically pure short branches is an efficient way to improve the poor crystallization kinetics of PLLA, which is one of the major drawbacks of this polymer. Graphical abstract: Image 1 Highlights: Optically pure short branches were grafted on poorly stereoregular commercial PLLA. Optically pure short chains crystallize faster and facilitate crystal growth of PLLA. Crystallization kinetics of PLLA can be enhanced by tailored chain structure.